Evaluation of Raw and Detoxified Neem Cake in the Diets of Wistar Rats (Rattus norvegicus) as Partial Protein Supplement - Nageswara Rao, S. B. (Indian Journal of Animal Nutrition, 2018)
Present experiments were conducted to test raw and detoxified neem cake as a replacement of soybean meal in the diets of Wistar rats, Replacement of up to 25 % soybean meal with DNC only resulted in positive growth rate (0.60 g/d) in rats compared to control (1.55 g/d). Low levels of DNC supplementation (12.5 % in experiment 1 and 25 % in experiment 2 caused similar nutrient intake and digestibility over control. DNC supplementation did not exert any abnormal changes in blood profiles except in elevated AST levels in 37.5% replaced group. Serum testosterone levels were found to be reducing in rats that received DNC at 50% and RNC at 25%. Mild changes in intestinal villi were observed up on histopathological examination in DNC 25 % group. Feeding of DNC is definitely better than RNC and replacement of SBM nitrogen with DNC up to 25 % only did not exert adverse changes to cause growth depression, decreased feed consumption, blood profiles and histopathology. Thus, DNC has to be fed with caution at low levels for monogastric animals.